2021
DOI: 10.1108/sbr-08-2020-0104
|View full text |Cite
|
Sign up to set email alerts
|

Remittances and households’ savings behaviour in Bangladesh

Abstract: Purpose The purpose of this study is to examine the impact of remittance inflow on households’ savings behaviour in Bangladesh. Remittances are considered as the countercyclical flow of income for its recipient economies. It surges the liquidity of the households receiving remittances, allows them to endure local economic shocks and facilitates them to practice productive activities. Remittances often form a big pool of resources for investment which complement the national savings and support the country’s gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 65 publications
1
6
0
Order By: Relevance
“…The development of a savings awareness campaign is also recommended to inform households of the importance of setting aside some of the remittances they get during times of low or no shock so that they can use those funds to finance consumption and non‐farm businesses during a crisis when it strikes. Profits from the revenues of these firms can improve a family's capacity to withstand financial adversity; thus, if a sizable amount of the remittance is set aside for savings, it can result in significant economic growth over time, as demonstrated in Salahuddin et al (2021) in the case of Bangladesh.…”
Section: Conclusion and Recommendationmentioning
confidence: 99%
See 1 more Smart Citation
“…The development of a savings awareness campaign is also recommended to inform households of the importance of setting aside some of the remittances they get during times of low or no shock so that they can use those funds to finance consumption and non‐farm businesses during a crisis when it strikes. Profits from the revenues of these firms can improve a family's capacity to withstand financial adversity; thus, if a sizable amount of the remittance is set aside for savings, it can result in significant economic growth over time, as demonstrated in Salahuddin et al (2021) in the case of Bangladesh.…”
Section: Conclusion and Recommendationmentioning
confidence: 99%
“…Remittances can be beneficial to households when they are put to different use by their recipients such as consumption and profitable business ventures as demonstrated in Salahuddin et al (2021) to enhance the welfare of households. According Salahuddin et al's (2021) report, when applied to businesses by recipients as shown in the case of Bangladesh, remittances can generate revenues, which can improve a household's capacity to withstand financial adversity. Thus, if a sizable amount of the remittances received by households is set aside for savings, it can result in significant economic growth over time.…”
Section: Remittancesmentioning
confidence: 99%
“…However, in comparison to international remittances, the impact of receiving internal remittances on the probability of a households' saving is weaker. Salahuddin et al (2021) also investigate the effects of remittances on households' savings behaviour. This study finds out that international remittances encourage households in Bangladesh to save in many forms, such as opening savings accounts, deposit pension schemes and savings at home.…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, in comparison to international remittances, the impact of receiving internal remittances on the probability of a households’ saving is weaker. Salahuddin et al. (2021) also investigate the effects of remittances on households' savings behaviour.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In general, quite a few papers have examined the effect of remittances on savings and expenditure patterns (see, e.g., Castaldo and Reilly 2007;Ang et al 2009;Tabuga 2010;Clément 2011;Haider et al 2016;Quartey et al 2019;Opiniano 2021;Salahuddin et al 2022). Both the life-cycle theory of Modigliani and Brumberg (1954) and the permanent income hypothesis proposed by Friedman (1957) have been influential with regard to the identification of possible relations among remittances, expenditures, and savings.…”
Section: Introductionmentioning
confidence: 99%